Research on the Microstructure and Mechanical Properties of Cr2O3/Cu Composites Prepared by Internal Oxidation and HP Method - Qinguo Zhou; Haijun Wu; Qi Zhao; Yichun Liu (Metals)
In this study, an innovative internal oxidation-powder metallurgy combined process was employed to controllably generate nano-sized Cr2O3 reinforcing phases within the Cu matrix. The Cu/Cr2O3 composites were successfully fabricated using the hot-press sintering (HP) method, and a systematic comparison was made between the microstructure and mechanical properties of composites prepared by internal oxidation and external addition methods. The results show that internal oxidation primarily occurs during the sintering process rather than ball milling. Compared with external addition, the internal oxidation method effectively prevents particle aggregation and achieves a uniform distribution of Cr2O3 particles in the Cu matrix. When the Cr content reaches 5 wt%, the Cu-5%Cr composite exhibits optimal mechanical properties, with a yield strength of 282.7 MPa and ultimate tensile strength of 355 MPa, representing increases of 43% and 34% over pure copper, respectively, while maintaining an elongation of 12.6%. The Cr2O3 particles generated via internal oxidation enhance their strength through Orowan strengthening and dislocation pinning, thereby significantly improving mechanical performance without compromising plasticity. This research provides a novel process optimization approach for developing high-performance dispersion-strengthened copper matrix composites.